Biological Impact of Exposure to Extremely Fine-Grained Volcanic Ash. (16th July 2018) - Aguilera, Cristina; Viteri, Marco; Seqqat, Rachid; Ayala Navarrette, Ligia; Toulkeridis, Theofilos; Ruano, Ana; Torres Arias, Marbel
Abstract : At the northwestern edge of South America is located Ecuador. This place is a classical example of an active continental margin with widespread active volcanism. Detailed studies about the impact of volcanic ash on human health are still lacking. Therefore, the disease of exposed populations is unknown. The objective of the present investigation was to assess the biological impact of Pichincha volcanic ash on cell culture and inflammation in murine lung tissues that will contribute to the understanding of the hazards. In this study, the in vivo phase was performed in mice C57BL/6 exposed to several doses of volcanic ash (0.5, 1, and 3.75 mg/100 g mouse body weight). The body weight and survival were controlled during seven days of treatment. The expression of inflammation markers NRLP 3, caspase-1, pro-IL-1, IL-1 β, IL-6, IL-8, and h-HPRT was analyzed. The in vitro phase was performed in lung cancer cells A549, peritoneal macrophages, and McCoy cells exposing them to different concentrations of volcanic ash (80, 320, and 1280  μ g/cm3) to determine the cytotoxicity and the production of reactive oxygen species. The ash initiated activation of the inflammasome complex NRLP 3 and the initiation of a proinflammatory activity in the murine lung tissue depending on the concentration of this agent. The viability of A549 and McCoy cell decreased with the length of exposure and increased with the concentration of volcanic ash. The activity in superoxide dismutase decreased by about 60%, leading to the formation of reactive oxygen species. These results associated with compounds contained in Pichincha volcanic ash are considered hazardous elements which induce inflammation leading to activate inflammasome NRLP, releasing reactive oxygen species, and producing changes in cell morphology and density, all of which are expression of cytotoxicity.